2014
DOI: 10.1136/ejhpharm-2013-000436.266
|View full text |Cite
|
Sign up to set email alerts
|

DI-095 Possible telaprevir-induced pancreatitis. A case study

Abstract: Background Telaprevir is one of the new drugs for chronic hepatitis C genotype 1. As it is a new drug is necessary to be aware of the emergence of new adverse reactions that may not be included in the SPC. Purpose To investigate possible severe adverse reactions not mentioned in telaprevir’s SPC. Materials and methods Descriptive and retrospective clinical case. Data were obtained by review of the patient medical history, Savac and Selene software and laboratory data. Results Fifty-seven-year-old male wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This analysis also found use of interferon to be associated with a higher prevalence of acute pancreatitis in patients with HCV infection (2.7%). Pancreatitis has also been observed in patients receiving telaprevir and boceprevir in combination with PR, and as an adverse event during treatment with sofosbuvir and ribavirin . In the telaprevir core clinical trial programme, pancreatitis was reported in 7/2669 (0.3%) patients treated with telaprevir in combination with PR; however, there were no cases of pancreatitis in the 764 patients treated with PR alone .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis also found use of interferon to be associated with a higher prevalence of acute pancreatitis in patients with HCV infection (2.7%). Pancreatitis has also been observed in patients receiving telaprevir and boceprevir in combination with PR, and as an adverse event during treatment with sofosbuvir and ribavirin . In the telaprevir core clinical trial programme, pancreatitis was reported in 7/2669 (0.3%) patients treated with telaprevir in combination with PR; however, there were no cases of pancreatitis in the 764 patients treated with PR alone .…”
Section: Discussionmentioning
confidence: 99%